PARENTAL INFLUENCE ON A CHILD'S GENDER IDENTITY DEVELOPMENT IN LAURIE FRANKEL'S THIS IS HOW IT ALWAYS IS - Rikhusshuba, Nazila; Huda, Miftahul (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2020)
Social aspects, including parents, are likely to influence the development of gender identity. As parents' actions and behaviours convey meaning to their children, they contribute to the formation of the children's gender identity development. The present study aims to investigate the parental influence on the gender identity development of a child character named Claude in Laurie Frankel's This Is How It Always Is. This study is a literary criticism concerning the issue of gender identity development in a literary work viewed from a psychological approach. The data were collected from a novel entitled This Is How It Always Is by Laurie Frankel and analyzed using the social cognitive theory of gender development by Bussey Bandura (1999). The results of the study revealed that his parents influence Claude's gender identity development through the process of modelling as a part of observational learning, which is also supported by parents' evaluative reactions such as rewards or punishments. The process of modelling reveals egalitarian gender roles and sexual orientation modelled and Claude's attention to his mother as an ideal female model, alongside with how parents convey affective reactions such as acceptance and approval on Claude's gender orientation.